Economic Downturn and the Improvement of Monetary Poverty and Social Exclusion Statistics System - Vaskis, Edmunds; Priede, Zaiga (Lithuanian Journal of Statistics, 2011)
The economic crisis has also challenged statistics. This article deals with the consequences of the economiccrisis for social statistics, and particularly monetary poverty indicators, which in this situation have shown certain signs ofweakness. The authors will discuss possible alternatives for the calculation of these indicators, as well as present theexperience of Statistics Latvia when reacting to the challenges raised by the economic crisis in the field of social statistics.